(untitled) (Journal of the College of Basic Education, 2022)
The research aims to identify the effectiveness of using a hospital program in recovering from muscle pain resulting from the use of force characterized by speed and measuring the pulse rate of young players in football. Of the young players in Al-Shula Sports Club for the sports season 2020/2021, which number (5) players in addition to (5) players from outside the basic research sample to conduct the exploratory experiment for research, the researcher conducted a survey study on a sample of the study community and outside the basic sample consisting of ( 5) Young football players under the same conditions as the basic research experiment in order to identify its suitability for application to the study sample and the objective of the study. One of the most important results was the use of cold baths as a healing method that leads to positive physical and physiological changes, and the study recommended the need to use a recovery program after training or the competitions have a positive effect on the speed of recovery.